Alfalfa dwarf cytorhabdovirus P protein is a local and systemic RNA silencing supressor which inhibis program med RISC activity and prevents transitive amplification of RNA silencing - Bejerman, Nicolas Esteban; Mann, Krin S.; Dietzgen, Ralf Georg (2017)
Plants employ RNA silencing as an innate defense mechanism against viruses. As a counter-defense, plant viruses have evolved to express RNA silencing suppressor proteins (RSS), which target one or more steps of the silencing pathway. In this study, we show that the phosphoprotein (P) encoded by the negativesense RNA virus alfalfa dwarf virus (ADV), a species of the genus Cytorhabdovirus, family Rhabdoviridae, is a suppressor of RNA silencing. ADV P has a relatively weak local RSS activity, and does not prevent siRNA accumulation.